Personality Determinants of Burnout Among Nurses: A Study at Nakuru County Referral Hospital - AYWAK, Charles; ROTICH, Abigael (KABARAK UNIVERSITY, 2020)
Workplace burnout is characterized as feelings of energy depletion or exhaustion; increased mental distance from one’s job, or feelings of negativism or cynicism related to one’s job; and reduced professional efficacy. The purpose of this study was to establish the relationship between personality traits and burnout among nurses at Nakuru County Hospital. A cross sectional study design was adopted. The majority of the respondents were fully employed (84%), aged 21-50+, gender 80.3% female, 47.4% single, 44.7% married. Most respondents (68.4%) attained ≤ Diploma while 31.5% had ≥ BSc.N with work experience of 1-≥15. Findings: Most of the nurses had traits of conscientiousness (44.7%) and agreeableness (34.2%). Overall, 44.2% of nurses had moderate-high emotional burnout, 77.6% depersonalization of moderate-high and 21% moderate-high decreased personal competence. Conscientiousness scored significantly high on emotional exhaustion (moderate-tohigh 36.6%) and depersonalization (moderate-to-high 34.1%). The agreeableness trait scored high on depersonalization ((moderate-to-high 36.6%). There is significant prevalence of burnout among nurses with conscientiousness and agreeableness personality traits. In-depth qualitative assessment of burnout experience among different personality traits among nurses is recommended.
FULL TEXT
Keywords: Burnout, emotional exhaustion, Decreased Personal Competence, conscientiousness, agreeableness.